Quasi-carbon taxation - The German eco tax and its impact on CO₂ emissions - Petrik Runst; David Höhle (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2021)
Many countries have only recently introduced carbon taxation to reduce emissions and the time series data for evaluating these policies is not available yet. Consequently, we use the imposition quasi-carbon-taxes in the German transportation sector, i.e. taxes on fuel that are not calculated based on actual CO2content but which raise the implicit price of carbon emissions, to evaluate the effectiveness of environmental taxation. Our results indicate that the carbon price increase by about 66 exteuro/t CO2led toa considerable decline of transport emissions by 0.2 to 0.35 t per person and year. Our quantitative results as well as a detailed qualitative analysis of a German car manufacturer's business reports suggests that the tax triggered an improvement in engine technology as well as an increased share of diesel engines.
Keywords: H23; Q48; R48; 330; Carbon taxation; transport sector; carbon emissions